Physical activity among nursing students during coronavirus disease 2019 pandemic, Nepal - Kumari Mandal, Punam; Yangden, Namita; Rai, Bhumika; Bhandari, Menuka; Paudel, Susan (Journal of Kathmandu Medical College, 2023)
Background: Reduced physical activity is one of the major factors affecting health and has been a serious global problem during coronavirus disease 2019 (COVID-19). Prolonged homestays can lead to increased sedentary behavior and reduced physical activity.Objectives: To assess the level of physical activity among nursing students.Methods: An analytical cross-sectional study was carried out on nursing campuses of Tribhuvan University in 2020 September 15 to 2020 December 15 among undergraduate students after Institutional ethical clearance using a self-administered structured International Physical Activity questionnaire. Samples of 255 students using proportionate systematic random sampling were included. Data analysis was done using SPSS version 17.0. The total score of physical activity was calculated and the level was categorised as low, moderate, and high. Ordinal logistic regression was used to find the association between the level of physical activity and selected demographic variables.Results: The study showed that engagement in vigorous physical activity was lower but the median time spent on moderate MET-Minutes/Week was 630 (1620-180). Likewise, (75, 29.4%) have low and (129, 49%) have a moderate level of Physical Activity. Furthermore, there is an association between the level of physical activity with the place of residence.Conclusion: The study concludes that more than one-third of respondents have a low level of physical activity. Furthermore, there is an association between the level of physical activity and place of residence. This reflects the need to sensitise nursing students to adopt physical activity in everyday life to improve general health and well-being during the COVID-19 pandemic.